Analisis dan Perancangan Aplikasi Chatbot dalam Pelayanan Penerimaan Mahasiswa Baru pada Perguruan Tinggi - Muhammad Rizki Herfian; Ahmad Rio Adriansyah (LPPM STT Terpadu Nurul Fikri, 2021)
This study aims to design and create a Chatbot that can answer general questions about New Student Admissions at Sekolah Tinggi Teknologi Terpadu Nurul Fikri (STT-NF). The benefit of this research is to help users or prospective new students to get information on New Student Admissions (PMB) at STT-NF. The research begins with Chatbot System Analysis and Literature Study on Chatbot Creation. Then the Chatbot is implemented using the Telegram Messaging API using the Python programming language. The program test using the Black Box Testing method while testing the user using the User Acceptance Testing (UAT) and Questionnaire methods. Based on the study results, it can conclude that the author has succeeded in designing and creating a Chatbot that can help users or prospective new students obtain information on New Student Admissions at the Sekolah Tinggi Teknologi Terpadu Nurul Fikri (STT-NF).